Modifikasi Desain MSR Menjadi PCMR Yang Lebih Kompetitif Dan Memiliki Sistem Keselamatan Melekat - Perpustakaan UGM, i-lib ([Yogyakarta] : Laboratorium aekologi Fak. Biologi UGM, 2006)
A study about PCMSR( Passsive Compact Molten Salt Reaktor) 1000 MWe design using LiF-BeF,-UF4-ThF4 (ThU233) molten salt fuel has been performed. This reactor is designed as a thermal breeder reactor. The neutronics calculation of the reactor core has been done with SRAC 95 computer code. This study is performed for equilibrium core with online extraction of Pa-233 and the fission product neutron poisons. Variations of core cell geometry and variation of 2330 enrichment in slight under moderated condition, become SRAC input. SRAC calculation result give criticality and conversion ratio values of 1,00863 and 1,02938 respectively for normal operation condition. The reactor has slight positive void coefficient for the range of void fraction value from zero (normal operation condition) to 22 %. For the range of void fraction value from 22 % to 50 % the void reactivity coefficient becomes slight negative. Above 50 % of void fraction, the void reactivity coefficient becomes large negative. Thus the overall value of the void reactivity is negative. Keywords : PCMSR, thermal breeder reactor, negative void reactivity